Diastereodivergent Synthesis of A-Ring Lactones Derived from Cholesterol and Diosgenin: A Convenient Solution for an Old Problem – NMR and X-ray Characterization - García-Santos, William H.; Valente-Valdovinos, Paola; Cortina-Mendoza, Álvaro J.; Flores-Álamo, Marcos; Iglesias-Arteaga, Martín A. (Synthesis, 2024)
A convenient protocol for the synthesis of A-ring lactones derived from cholesterol was developed. A lactone reduction–lactol separation–reoxidation sequence, applied to the inseparable mixture of diastereomeric lactones, allows the production of multigram amounts of each lactone in pure form. The same sequence applied to A-ring lactones derived from diosgenin produced similar results. A detailed NMR characterization of all the obtained lactones is also provided. X-ray diffraction corroborated the structure of the obtained compounds.
Keywords: steroids; epimeric lactones; lactols; NMR analysis; X-ray diffraction